2021 Physics Education Research Conference Proceedings 2021
DOI: 10.1119/perc.2021.pr.santana
|View full text |Cite
|
Sign up to set email alerts
|

Negative impacts of an unwelcoming physics environment on undergraduate women

Abstract: This research focuses on the experiences of three undergraduate white women who are physics and astronomy majors. Specifically we conducted semi-structured, empathetic interviews which reveal how uncomfortable physics environments inside and outside of the classroom exclude undergraduate women. The women give accounts of the behaviors of their male peers and instructors that influenced the physics culture. We use standpoint theory to focus on the experiences of undergraduate women to provide a holistic perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…We note that Models 2 and 3, in which perceived recognition is predicted by self-efficacy and interest, are not supported by our prior interview findings Li & Singh, 2023) showing that perceived recognition may be an important driver of the other two constructs. Our interviews show that women were less likely than men to feel positively recognized by physics instructors/TAs, and this lack of recognition or discouraging feedback from instructors/TAs deteriorated their self-efficacy, and lowered perceived recognition and self-efficacy further lowered their interest Li et al, 2020;Santana & Singh, 2021). This experience made the female students wonder whether it was because their questions were not good or too easy, and thus they started doubting their ability to do well in their courses.…”
Section: Instructional Implications Of the Statistically Equivalent M...mentioning
confidence: 83%
See 1 more Smart Citation
“…We note that Models 2 and 3, in which perceived recognition is predicted by self-efficacy and interest, are not supported by our prior interview findings Li & Singh, 2023) showing that perceived recognition may be an important driver of the other two constructs. Our interviews show that women were less likely than men to feel positively recognized by physics instructors/TAs, and this lack of recognition or discouraging feedback from instructors/TAs deteriorated their self-efficacy, and lowered perceived recognition and self-efficacy further lowered their interest Li et al, 2020;Santana & Singh, 2021). This experience made the female students wonder whether it was because their questions were not good or too easy, and thus they started doubting their ability to do well in their courses.…”
Section: Instructional Implications Of the Statistically Equivalent M...mentioning
confidence: 83%
“…In this study, we propose a SEM model in which perceived recognition predicts self-efficacy and interest, and self-efficacy predicts interest. This model draws inspiration from our previous qualitative research (Doucette, Clark & Singh, 2020;Li & Singh, 2023;Santana & Singh, 2021) and other researchers' studies (Bandura, 1994;Hidi & Renninger, 2006). For example, prior research has shown that self-efficacy is influenced by encouragement or discouragement related to one's performance or ability (Bandura, 1994).…”
Section: Physics Identity Frameworkmentioning
confidence: 97%
“…Recent studies by Santana and Singh suggest that students from underrepresented groups often experience a lack of sense of belonging within physics [11]. In a previous study, the authors suggested that due to the hostile environment created by male peers in physics, it is critical for women to create a community amongst themselves and have resources readily available to support this [12]. Though both studies underscore how underrepresented populations feel unwelcome in physics, they did not investigate how these experiences af-fected students' decisions to stay in or leave physics.…”
Section: Introductionmentioning
confidence: 99%
“…Part of this disproportionately low representation is attributed to a "cold" and unwelcoming climate within physics departments towards women and students of color [5][6][7]. Prior research indicates this is partly due to their white male peers' and instructors' attitudes, as well as an unawareness within the culture of physics toward the differential experiences that marginalized groups face [8][9]. Additional contributions to the lack of women and students of color in physics come from dissimilar pre-college experiences.…”
Section: Introductionmentioning
confidence: 99%